Análise e reforço sísmico de Igrejas da ilha do Pico - António Arêde (2008)
This chapter reports on an integrated strategy for modelling, experimental calibration, numerical analysis and seismic strengthening pursued on two churches of Pico Island, Azores, namely the Bandeiras and the Madalena churches. Following an initial description of observed damages after the 1998 earthquake, different modelling options are outlined. Vibration frequencies and mode shapes were experimentally obtained and compared with numerical ones for calibration purposes. Seismic analysis were carried out using the records of that earthquake and the results were analysed in light of the observed damages. Numerical findings helped on the proposal and design of the seismic strengthening that is also thoroughly described and illustrated.